Metastatic breast cancer to the thyroid diagnosed by fine-needle aspiration cytology: A case report and literature review - Zhaohui Yang; Xiaobo Cai; Xuequan Cao; Chengquan Zhao; Hongsheng Lu (Elsevier, 2022)
Metastatic breast cancer to the thyroid is rare. We report a case of breast cancer that metastasized to bilateral thyroid. A 62-year-old woman who was admitted due to thyroid nodules identified by ultrasound. Ultrasound revealed multiple thyroid nodules with calcification, which were classified as TI-RADS 4c. She had a history of left breast cancer 5 years ago, treated with radical mastectomy and adjuvant EC-TH chemotherapy and radiotherapy. The patient underwent fine-needle aspiration of bilateral thyroid nodules, and the cytology examination revealed a metastatic ductal carcinoma of breast. The findings indicate that cytological morphology, immunohistochemistry and molecular test are important for diagnosis of thyroid metastatic carcinoma.